Towards a Reinterpretation of Eunuchs as “Third Gender” in Ancient Eastern Mediterranean. - González Palacios, Héctor (My University, 2024)
During the 1990s and early 2000s, the concept of the third gender became popular in Anthropology as a reaction to the binary approach of Western Ethnography in the study of other societies. The idea of "third genders" spread not only in the study of contemporary societies, but also in the study of past societies, from Byzantium (e.g., in the work of Katherine Ringrose), to the ancient Near East (e.g., in Ilan Peled's book on eunuchs, among others). In this paper we propose the need to move forward and leave behind the concept of "third gender". In our opinion, this term, which arose in an embryonic moment of Queer Studies, had its logic as a reaction to the limiting binarism that had been preeminent up to that time, but today it constitutes a constrain. This is because the category of "third gender," like binarism, is a contemporary metahistorical construct, which, at an effective level, discourages knowledge of local ways of understanding and classifying gender. For our part, we propose three key factors when studying gender in eunuchs and, in general, in ancient societies: • To question the given Western categories, including also terms such as "man" and "woman", in favor of local terms. • To understand gender as a set of performative actions, so that it only exists as a constant performance between individuals. • To replace absolute and permanent categories ("genders") with a plastic and contextual understanding of gender. In our case, we will focus mainly on the eunuchs of the Proto-Byzantine period (3rd-7th centuries), which constitute our area of expertise and are to a large extent the beginning of a tendency in recent historiographical research to classify eunuchs as a third gender, due to the work of K. Ringrose. Our intention is not to deny absolutely the possibility of intermediate categorizations in gender, but to put in the center the importance of understanding gender in a more complex way.
Keywords: Eunucos; Rol sexual; Historia antigua; Eunuchs; Antiquity; Byzantium; Gender studies; Third Gender